Guidance and Practice in the Diagnosis and Management of Two Rare Inherited Metabolic Diseases - Kazakova, Alessia (Université d'Ottawa / University of Ottawa, 2018)
By facilitating timely diagnosis and treatment initiation, population-wide newborn screening programs have led to important reductions in morbidity and mortality for many rare diseases, including medium-chain acyl-CoA dehydrogenase (MCAD) deficiency and very-long-chain acyl-CoA dehydrogenase (VLCAD) deficiency. Newborn screening has also expanded the spectrum of disease severity for MCAD and VLCAD deficiencies to include a higher proportion of milder cases, raising questions about appropriate disease management. To date there has been no systematic attempt to characterize best management practices in terms of the guidance that is available to those who provide care for MCAD and VCLAD deficiencies; nor has there been an attempt to understand the extent to which current practices align with such currently available guidance. The two projects that are part of this thesis sought to address these research gaps with a particular focus on two key disease-specific management practices we identified in advance as priorities: the use of carnitine supplementation and the recommended duration of fasting. The objective of the first project was to systematically review the quality and content of clinical practice guidelines and/or recommendations for the diagnosis and management of both MCAD and VLCAD deficiencies. Two independent reviewers assessed the eligibility of citations retrieved from a comprehensive search of the peer-reviewed and grey literature. We appraised the quality of the reviewed guidance and extracted information on the content of recommendations. From the 25 guidance documents that met our inclusion criteria, only 7 incorporated evidence reviews, indicating that guidance in this field does not generally meet established methodological standards for the rigorous development of clinical practice guidelines. With respect to content, we identified unclear and inconsistent recommendations regarding fasting times and the use of carnitine supplementation. Further empirical evidence in these areas is necessary to inform the development of future rigorous guidelines. The objective of the second project was to identify actual practices in the management of MCAD deficiency. We conducted a scoping review of published literature on treatment practices around the world and a secondary analysis of data documenting treatments received by participants in a Canadian pediatric cohort study. For the scoping review, citations retrieved from our comprehensive search strategy were screened by two independent reviewers. We extracted information on study characteristics and disease management. Our secondary analysis included longitudinal data for Canadian children with MCAD deficiency, born between 2006 and 2015 and enrolled in a cohort study at one of 13 centres. For both project components, we described carnitine supplementation and fasting times, overall and according to potential indicators of disease severity (genotype, biochemical phenotype). We identified 5 relevant publications in the scoping review and analyzed data for 107 children participating in the Canadian cohort. Management practices related to carnitine supplementation and fasting times for MCAD deficiency were highly variable based on both data sources. There was some evidence of an association between genotype and carnitine use, which, based on the scoping review, may be due to a relationship between genotype and carnitine deficiency. While actual practice was in some ways aligned with the guidance we reviewed in the first project, these results underscore the need for further evidence to address areas of uncertainty that have been prioritized by patients and families, clinicians, and health researchers, including questions regarding the potential to tailor treatment to predicted disease severity and an emphasis on controversial therapies such as carnitine supplementation.
Keywords: Inherited Metabolic Diseases; Fatty Acid Oxidation Disorders; Guidelines; Current Practice; Canadian cohort analysis